Biosynthesis of phyto-functionalized silver nanoparticles using olive fruit extract and evaluation of their antibacterial and antioxidant properties - Ullah, Sami; Khalid, Rimsha; Rehman, Muhammad F.; Irfan, Muhammad I.; Abbas, Azhar; Alhoshani, Ali; Anwar, Farooq; Amin, Hatem M. A. (Frontiers Media SA, 2023)
The green synthesis of nanomaterials is of utmost interest as it offers an eco-friendly approach over chemical synthetic routes. However, the reported biosynthesis methods are often time-consuming and require heating or mechanical stirring. The current study reports a facile one-pot biosynthesis of silver nanoparticles (AgNPs) mediated by olive fruit extract (OFE) and sunlight irradiation of only 20 s. OFE acts as both a reducing and a capping agent for the formation of OFE-capped AgNPs (AgNPs@OFE). The as-synthesized NPs were systematically characterized by UV-vis spectrometry, Fourier transform infrared (FTIR) spectroscopy, scanning electrochemical microscopy with energy-dispersive X-ray (SEM-EDX), X-ray diffraction (XRD), dynamic light scattering (DLS), and cyclic voltammetry. SEM images confirmed the successful formation of monodispersed spherical AgNPs@OFE of approximately 77 nm. FTIR spectroscopy suggested the involvement of functional groups of phytochemicals from the OFE in the capping and reduction of Ag+ to Ag. The particles revealed excellent colloidal stability as evidenced from the high zeta potential (ZP) value (ˆ’40 mV). Interestingly, using the disk diffusion method, AgNPs@OFE revealed higher inhibition efficiency against Gram-negative bacteria (Escherichia coli, Klebsiella oxytoca, and extensively drug-resistant (XDR) Salmonella typhi) than Gram-positive bacteria (Staphylococcus aureus), with Escherichia coli showing the highest inhibition zone of 27 mm. In addition, AgNPs@OFE exhibited maximum potent antioxidant scavenging potential against H2O2, followed by DPPH, O2ˆ’, and OHˆ’ free radicals. Overall, OFE can be considered an effective source for the sustainable production of stable AgNPs with potential antioxidant and antibacterial activities for biomedical applications.